Impact of climate change and irrigation development on hydropower supply in the Zambezi River Basin, and implications for power sector development in the Southern African Power Pool - Spalding-Fecher, Dennis Randall (Energy Research Centre, 2018)
This thesis investigates the hypothesis that the combination of future changes in climate and development (primarily irrigation) in the Zambezi River Basin (ZRB) threatens the technical and economic viability of existing and planned hydropower plants, and in turn the expansion plans and costs of the regional power system for Southern African countries. This hypothesis is evaluated using the following three questions to structure the analysis. ● How could future climate and irrigation expansion in the Zambezi River Basin affect hydropower generation potential? ● How could development in Southern Africa affect power demand, and how might this demand be met? ● How could the changes in water availability for hydropower (i.e. due to climate change and development) affect regional electricity expansion plans, generation costs and greenhouse gas emissions? The methodological tool used to address the first research question is the Water Evaluation and Planning (WEAP) scenario modelling system, developed by Stockholm Environment Institute. WEAP is a combined hydrological and water allocation model that is widely used internationally. The modelling demonstrates that the change in future climate is the overwhelming driver of future production at almost all hydropower plants in the ZRB over the study period of 2010-2070. The difference in mean generation under wetting and drying climates (i.e. difference between the values under wet and dry scenarios) is 12-16% for individual existing plants. This difference is as much as 30% for individual new plants, with all plants other than Batoka showing variation in mean annual generation of more than 13%. The impact of irrigation, on the other hand, is mainly an issue for plants downstream from Kariba, and even then the magnitude is typically less than a third of the impact of the alternative climates. The water modelling results therefore do not vary significantly across alternative development futures, because the accelerated irrigation development is still not large enough to dramatically impact hydropower. The second research question is analysed using Stockholm Environment Institute's Long- Range Energy Alternatives Planning (LEAP) model to trace the impacts of socio-economic development on electricity supply and demand. The analysis combines a simulation of current utility plans with a least cost optimisation to meet the remainder of supply needed over the long term. The analysis shows that the underlying socio-economic drivers of demand lead to both a dramatic increase in total electricity demand and a shift across sectors and countries within the region. Total electricity demand for the Southern African Power Pool (SAPP) region increases by 8-14 times over period from 2010 to 2070, with the combined demand from the rapidly growing countries of Democratic Republic of Congo (DRC), Mozambique and Zambia becoming larger than South African demand by 2070. At the sectoral level, the share of total demand from the extractive and manufacturing sectors increases from 59% in 2010 to 70% in 2070 under the most optimistic development scenario, based on a compound annual growth rate of consumption in excess of 5%. Activity level growth is the main driver of demand growth. Comparison with other studies in the region show that the mid-term demand estimates (e.g. 2025-2030) in this study are generally within the range of other research, with somewhat higher demand estimates from the most optimistic development scenario. Total electricity supply required over the longer term is met through the addition of 400-1400 GW of new capacity, or 8-20 times the current capacity of the region. More strikingly, the power mix shifts from almost 80% coal-fired power to 24-44% coal by 2070, with the balance being supplied mainly by solar, wind, hydropower and nuclear generation. The regional shift is no less dramatic, with South Africa's share of total generation declining from 84% to only a third, based on the higher growth rates in countries such as DRC, Mozambique and Zambia. The third research question is the most important in terms of the original contribution of this PhD thesis. Applying the WEAP and LEAP tools to an integrated multi-country system is a methodological advance pioneered in this thesis, showing that the integrated methodology can provide information to address not only the immediate questions about generation choices under an uncertain future climate, but also system costs and GHG emissions. The analysis shows that the reduction in hydropower generation under a drying climate leads to a shift in both capacity expansion choices and the operation of the regional power system, while the increases in hydropower output under a wetting climate are smaller. In other words, the "downside" of future climate changes is larger than the potential "upside". At an aggregate level, the increases in generation costs are a small share of total generation costs (i.e. less than 1% over the full study period compared to the baseline climate). However, the impact on generation costs for hydro-dependent countries such as Mozambique, Zambia and Zimbabwe is considerably larger, and these countries also gain more under a wetting climate. Finally, because some hydropower could be displaced by coal, regional GHG emissions could increase by more than 6 MtCO2 per year in the medium term, or the equivalent of a large coalfired power station. This research has important policy implications for the water and electricity sector in the region. The potential transformation of the electricity supply sector would require a fundamental shift in resource use, grid management and infrastructure development in the region. The shift in the resource base for electricity generation will pose challenges for grid integration and balancing supply and demand across countries and load centres. Historically, the development of transmission capacity, and the resulting trade in electricity, has been constrained by the political and economic realities of the region. There are signs that the politics could be shifting, however, for political, economic and environmental reasons. In addition, the relatively low consumption of water in the Zambezi River Basin in the past meant that explicit trade-offs across sectors and across countries posed less of a challenge for the basin overall. This is very likely to change in the future, as increased demand from all sectors, and major potential changes in climate will require more explicit agreements across both countries and user groups on how best to utilise a limited resource. This research demonstrates the tools that could be used to integrate both climate change and upstream development demands into the feasibility studies before investment decisions are made. The research also illustrates the first steps toward integrating climate change and upstream development considerations into national and regional electricity planning. The electricity and water sectors are important contributors to the development of the Southern Africa, and hydropower in the ZRB lies at the intersection of these fields. Climate change, however, has the potential to add increased stress on these sectors, both directly and indirectly, and yet is not being considered in many individual hydropower power investments, or in national or regional electricity planning. The integrated scenario analysis approach in this thesis demonstrates how the impacts of climate change, as well as increased irrigation demand for water, could be assessed not only for specific hydropower plants and for the entire sector power sector. Preparing for this possible range of future climates can increase the resilience of the sector and reduce the risk of stranded assets in the power sector.